ANALISIS USABILITY DAN PERBAIKAN ANTARMUKA APLIKASI SCLEAN MENGGUNAKAN METODE HUMAN CENTERED DESIGN - Lidya Yunike Yauw; Ahyar Muawwal; Arfan Yunus (STMIK KHARISMA Makassar, 2021)
The SCLEAN application is an online laundry service application that aims to bring together laundry business owners and laundry service users, so that consumers have no difficulty in delivering or finding a laundry place. In an effort to introduce the SCLEAN application in the community, researchers conducted surveys and interviews with several potential users and found several problems with the SCLEAN application interface, such as: 1) In the account section, it was not possible to change the data on the profile photo, name, and phone number section; (2) There is no assessment section that can be made by the customer to the laundry service provider; (3) There is no help regarding the application; (4) there is no icon menu name. The problems that have been found have become the basis for research to conduct usability analysis using the Human Centered Design method and PSSUQ as a questionnaire to assess the level of user satisfaction. From the evaluation results, a solution design is made based on the problems that have been obtained. The comparison results show an increase in the aspect of effectiveness from 80% to 100%, the efficiency aspect of the average processing time from 15.4 to 14.38 seconds, and the aspect of user satisfaction from 72% to 89.87%. From these results, the researcher concludes that the improved design has increased the user experience value compared to the previous design.